Treatment of MTBE in wastewater by air stripping and carbon adsorption - Mohamad Noradli, Hashim (2010)
A study was conducted on the efficiency of the combined system for removal of the Methyl-tert-butyl ether (MTBE) from wastewater by simultaneous use of air stripping and carbon adsorption. MTBE which is widely used in industrial may cause environmental concern due to its presence in waste water. Two main processes involve in this research. These processes are air stripping and carbon adsorption. Compressed air is used in air stripping process and the Granular Activated Carbon is for adsorption where adsorption of MTBE occurs on the GAC. This research is about to use combine system and remove pollutant from the wastewater, where combination of air stripping and activated carbon adsorption in remove MTBE from wastewater was analyzed. The experimental rig experiments conducted at different flow rates 4 and 6 (L/min). It conducted at different open valve time that is 30s, 40s, 50s, 60s, 120s, 180s and 240s. The highest removal for flow rate 4 is 85% at cycle time 240s and for flow rate 6 is 90% for cycle time 240s. The removal of the surfactant MTBE from water by simultaneous use of air stripping and powdered granular carbon, GAC adsorption shows better performance than other system. From this research It can be concluded that, the overall project achieve the objectives by completion. The combine system effectively removes MTBE from waste water. Hope the environmental problem also will be reduced by treat the waste water contain MTBE before it is release to natural water sources.